Investigation on Natural Infection of Covert Mortality Nodavirus in Large Yellow Croaker, Larimichthys crocea - Xu, Tingting; Fan, Yuding; Jia, Tianchang; Wang, Chong; Wang, Wei; Li, Jun; Zhang, Qingli; Yao, Cuiluan (Frontiers in Marine Science, 2022)
Covert mortality nodavirus (CMNV) recently became more prevalent, severely affecting farmed shrimps, and also other invertebrates and teleost fish, in the coastal areas of China. For better understanding of its prevalence and susceptibility of large yellow croaker Larimichthys crocea to CMNV, an epidemiological survey was carried out in the main producing areas (Ningbo, Zhejiang, China, and Ningde, Fujian, China) and its offshore feeding grounds in the Southern Yellow Sea. The collected cultured L. crocea individuals showed clinical symptoms such as anorexia and abnormal swimming and diagnosed for CMNV infection by using RT-nPCR assay. The positive rates for CMNV in the collected L. crocea samples from Ningbo, Ningde, and the Yellow Sea were 14.29% (4/28), 20.00% (7/35), and 16.67% (1/6), respectively. Furthermore, CMNV diagnosis using TaqMan probe-based reverse transcription quantitative PCR (TaqMan RT-qPCR) yielded positive rates of 25.00% (7/28), 22.86% (8/35), and 16.67% (1/6) respectively in the above-mentioned samples, and with a range of 12.73–3,108.33 of CMNV copy numbers/μg total RNA. Phylogenetic tree analysis based on the RNA-dependent RNA polymerase (RdRp) and capsid protein genes showed that CMNV isolates from L. crocea samples were clustered tightly with the original isolate of CMNV from Penaeus vannamei. The histopathological studies indicated that severe cellular necrosis occurred in the heart, liver, spleen, eye, and gill of naturally infected fish. Stronger positive signals for CMNV-specific probes appeared in the necrotic cells and tissues in the in situ hybridization (ISH) analysis. Transmission electron microscopy (TEM) revealed the presence of numerous 30 nm diameter CMNV-like viral particles. The purified CMNV suspension could cause a significant cytopathic effect (CPE) in epithelioma papilloma cyprini (EPC) cells and resulted in the formation of typical inclusion bodies, and also visible CMNV particles around the lysed EPC cells under the TEM. Taken together, all results of this study demonstrated that L. crocea is susceptible to CMNV. The prevalence of CMNV and its potential impacts on the wild population of L. crocea see the need for further investigations.